The pattern of internal and external political behavior of government sector managers with a political intelligence approach (case study: municipalities of Khorasan Razavi province) - Hamooni, Seyyed Arman; Taheri Lari, Masood; Bahramzadeh, Hasanali (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2021)
Background and purpose: In municipalities, due to the large scale and volume of human resources, which are the most skilled and specialized forces. Managers need to use all kinds of strategies and political skills to maximize the use of these resources to improve the organization’s performance, which is considered its main capital. Therefore, this research aims to present the model of intra-organizational and extra-organizational political behaviors of public sector managers with the approach of political intelligence in the municipalities of Razavi Khorasan province. Methodology: The current research is a developmental-applied, hybrid, and mixed exploratory research, combining qualitative and quantitative methods. In the qualitative part, the statistical population includes all professors of the management group and senior managers of the municipalities of Razavi Khorasan province in 2017. Twenty qualified people were included in the statistical population framework of the qualitative section, and finally, the information of 17 people was analyzed. In the quantitative part, the statistical population includes all the senior managers of the municipalities of Razavi Khorasan Province, and according to the statistics and information received from the municipalities of Razavi Khorasan Province, in 2016, 366 managers were working in 73 cities of Razavi Khorasan Province. They were. According to Cochran’s formula, the required sample size is approximately equal to 191 municipal managers of Razavi Khorasan province. In the qualitative part, the dimensions and components of intra-organizational and extra-organizational political behaviors and political intelligence were determined by reviewing and reviewing second-hand sources (articles and books). In the qualitative part, we examined the research questions. The data were analyzed by structural equations and with the help of AMOS software. Results: According to the results of the research, the dimensions of intra-organizational and extra-organizational political behaviors and political intelligence were investigated, and the components were identified, and finally, the results showed that political intelligence has an effect of 0.84 on the political behavior of managers. In this way, by improving the political intelligence of managers, it is possible to predict their political behavior to the extent of 0.84. Conclusion: In order to improve the ambiguous attitude of the managers of Khorasan Razavi province, it is suggested that the managers clarify the employment conditions for newcomers and that contracts are concluded transparently.